2022
DOI: 10.1002/imt2.57
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition in the sympatric and diet‐sharing Drosophila simulans and Dicranocephalus wallichii bowringi shaped largely by community assembly processes rather than regional species pool

Abstract: Clarifying the mechanisms underlying microbial community assembly from regional microbial pools is a central issue of microbial ecology, but remains largely unexplored. Here, we investigated the gut bacterial and fungal microbiome assembly processes and potential sources in Drosophila simulans and Dicranocephalus wallichii bowringi, two wild, sympatric insect species that share a common diet of waxberry. While some convergence was observed, the diversity, composition, and network structure of the gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…This suggested that the encounter between the two Sirex species may have remodeled the larval gut microbiome. Similar results demonstrating the importance of stochastic processes were also observed in studies on gut microbial communities in Drosophila simulans and Dicranocephalus wallichii bowringi [ 39 ]. Another study also showed that Curculio chinensis gut microbiome was derived from the surrounding environmental microbiome and was more affected by the microbiome from soil than that from fruits [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…This suggested that the encounter between the two Sirex species may have remodeled the larval gut microbiome. Similar results demonstrating the importance of stochastic processes were also observed in studies on gut microbial communities in Drosophila simulans and Dicranocephalus wallichii bowringi [ 39 ]. Another study also showed that Curculio chinensis gut microbiome was derived from the surrounding environmental microbiome and was more affected by the microbiome from soil than that from fruits [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…The microbial community assembly processes were qualified according to a previous study . Null model analysis was used to quantify the deviations of absolute phylogenetic distances from the random phylogenetic distance.…”
Section: Methodsmentioning
confidence: 99%
“…Exploring microbiome specificity is crucial for understanding ecological roles, diagnosing diseases, unraveling evolution, and exploring biotechnological potential [ 15 , 29 , 30 , 31 , 32 , 33 ]. An interactive flower plot serves as a valuable tool to display both common shared and unique sets among more than 10 microbiome sets, offering an alternative method.…”
Section: Case Demonstrationmentioning
confidence: 99%